2016
DOI: 10.1089/gtmb.2015.0148
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship BetweenADIPOR1Variants and the Susceptibility of Chronic Metabolic Diseases in a Northeast Han Chinese Population

Abstract: Objective: Shared genetic variants in ADIPOR1 have been identified as closely related to coronary artery disease (CAD), type 2 diabetes (T2D), and T2D with CAD susceptibility, suggesting that these variants are strong candidates for the common soil hypothesis. Therefore, it is essential to analyze the relationship between ADIPOR1 variants and the susceptibility to CAD, T2D, and T2D with CAD in other populations.Materials and Methods: A case–control study was conducted which included three case cohorts [CAD (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In this regard, common ADIPOR1 gene variants have been implicated with CHD in non-diabetic Asian subjects [ 63 , 67 ]. Likewise, the gene also has a significant association with CHD in T2D.…”
Section: Genetic Factors Associated With Chd Risk In T2d Asian Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, common ADIPOR1 gene variants have been implicated with CHD in non-diabetic Asian subjects [ 63 , 67 ]. Likewise, the gene also has a significant association with CHD in T2D.…”
Section: Genetic Factors Associated With Chd Risk In T2d Asian Populationsmentioning
confidence: 99%
“…Among the Northeast Chinese population, three out of six ADIPOR1 variants were markedly associated with a higher CHD risk. They include rs3737884*G (OR: 2.69), rs16850797*C (OR: 1.44), and rs7514221*C (OR: 1.75) [ 67 ]. However, there was no assessment of the genotypic impact on clinical variables performed in the study [ 67 ].…”
Section: Genetic Factors Associated With Chd Risk In T2d Asian Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Jin et al (2014) found an association between two SNPs in ADIPOR1 (rs3737884 and rs16850797) and T2DM in a Chinese population [53], and recently another study successfully replicated these findings with subjects from Northeastern China. Moreover, a third SNP (rs7514221) in ADIPOR1 was also found to be associated with an increased risk of T2DM [54].…”
Section: Discussionmentioning
confidence: 96%